PATIENTS 'PREFERENCES AND EXPERIENCES IN CHOOSING THE MODEL OF NORMAL LABOR CARE - Sri Styaningsih; Dwi Izzati Budiono; Muhammad Ardian Cahya (UNIVERSITAS AIRLANGGA, 2021)
AbstractBackground: In the last few decades the trend of work has shifted from normal delivery to Sectio Caesarea (SC), this is evidenced by the increasing incidence of CS deliveries in various countries. cesarean delivery without medical indications is one of the biggest factors causing cesarean delivery, this is due to the fear of normal labor pain. However, in developing countries, women still see a lot of interest in being able to be born normally, so the purpose of this study is to find out preferences and research experiences in choosing a normal delivery care model. Methods: The method used is a qualitative research by exploring, with the population is postpartum mothers who are in the target area of the Tuban Public Health Center and the Semanding Health Center, Tuban, East Java. The total respondents in this study were 8 respondents, the results of interviews with 8 respondents were then analyzed by transcribing verbatim, making general points, noting ideas that arise, and indexing or coding. Results: 1) preference for places of occurrence, geographical and economic factors, 2) preference in choosing a model that is carried out by a fast recovery process, and feeling like a real mother. 3) The preference for stress helpers is influenced by experiences from other families. Conclusion Preferences for nursing care models can affect the mother's decision making in choosing a nursing care model that can have an impact on her delivery experience